TINGKAT PENGANGGURAN TERBUKA MEMEDIASI DAMPAK INDEKS PEMBANGUNAN MANUSIA, PRODUK DOMESTIK REGIONAL BRUTO DAN UPAH MINIMUM KABUPATEN/KOTA TERHADAP KEMISKINAN - Encep Saefullah; Muhammad Angga Anggriawan (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
The purpose of this study is to analyze poverty and determine the impact of the Human Development Index (IPM) variable, Gross Regional Domestic Product (GRDP), Regency/City Minimum Wage (UMK) on Poverty in Banten Province with Open Unemployment Rate (TPT) as a Mediation Variable . The analytical tool used is PLS SEM analysis. Based on the analysis of the number of poor people in Banten province in 2021, it still shows a high poverty rate of 6.66%, an increase compared to the previous year. From the results of the study, it can be explained that the variables HDI (X1), GRDP (X2) and UMK (X3) have a direct impact on the Poverty variable (Y) of 99.3%, and the indirect impact on the variables HDI (X1), GRDP (X2) and UMK (X3) through TPT (Z) on the variable Poverty (Y) of 93.6%. Furthermore, the discussion is explained further in this study